Elevated Serum Growth Differentiation Factor 15 Levels in Hyperthyroid Patients - Zhao, Jiejie; Li, Min; Chen, Ying; Zhang, Shengjie; Ying, Hao; Song, Zhiyi; Lu, Yan; Li, Xiaoying; Xiong, Xuelian; Jiang, Jingjing (Frontiers in Endocrinology, 2019)
Background: Recent studies have shown that growth differentiation factor 15 (GDF15), a member of the transforming growth factor-(TGF-) /bone morphogenetic protein (BMP) superfamily, plays an important role in appetite, type 2 diabetes and cardiovascular diseases. Since thyroid hormone has pleiotropic effects on whole-body energy metabolism, we aimed to explore the effect of thyroid hormone on circulating GDF15 levels in humans and GDF15 genes expression in C57BL/6 mice. Methods: A total of 134 hyperthyroid patients and 105 healthy subjects were recruited. Of them, 43 hyperthyroid patients received thionamide treatment for 3 months until euthyroidism. Serum GDF15 levels were determined using the enzyme-linked immunosorbent assay (ELISA) method. To determine the source for the increased circulating GDF15, C57BL/6 mice were treated with T3, and GDF15 gene expressions in the liver, skeletal muscle, brown adipose tissue (BAT), inguinal white adipose tissue (iWAT), epididymal white adipose tissue (eWAT) were analyzed by quantitative real-time polymerase chain reaction (PCR). Results: Serum GDF15 levels were significantly elevated in hyperthyroid patients as compared with healthy subjects (326.06 ± 124.13 versus 169.24 ± 82.96 pg/mL) (P < 0.001). After thionamide treatment, GDF15 levels in hyperthyroid patients declined markedly from 293.27 ± 119.49 to 118.10 ± 71.83 pg/mL (P < 0.001). After adjustment for potential confounders, serum GDF15 levels were independently associated with hyperthyroidism. T3 treatment increased GDF15 expression in the brown adipose tissue of C57BL/6 mice. Conclusions: Serum GDF15 levels were elevated in patients with hyperthyroidism and declined after thionamide treatment. Thyroid hormone treatment upregulated GDF15 expression in mice. Therefore, our results present the clinical relevance of GDF15 in humans under the condition of hyperthyroidism.